Effect of Drying Using Solar Energy and Phase Change Material on Kiwifruit Properties - Reyes-Salinas, A; Mahn-Osses, A; Vasquez-Fajardo, J; Pailahueque-Barahona, N (Taylor and Francis Inc., 2019)
Solar energy has great potential as an alternative energy source, but variations in solar radiation require the use of additional energy sources to maintain a continuous drying process. We developed a process for drying kiwifruit using a solar dryer and an energy accumulation system with paraffin wax as phase change material. The final moisture content, total polyphenols, and antioxidant capacity were evaluated and compared with freeze drying. The analyzed experimental factors were kiwi slice thickness and the use or nonuse of fuzzy logic control systems to regulate the air flow through the devices. Critical moisture content, shrinkage, solar panel, and solar energy accumulator efficiencies were calculated. In addition, five empirical models were fitted to the drying curves. The solar panel showed an efficiency between 56 and 76%. The use of the fuzzy logic control system extended the period of available energy, thus prolonging the use of the solar panel and solar energy accumulator and using only 10% of the stored energy; otherwise, without the control system, 43% of the stored energy was used. The highest drying rates were achieved for kiwifruit slices 4 mm thick, using the solar dryer with the control system. The loss of polyphenols and antioxidant capacity were minimal for kiwifruit slices of thickness 8 mm without the control system. © 2018, © 2018 Taylor & Francis.